Multimodal Communication in an Early Childhood Bilingual Education Setting: A Social Semiotic Interaction Analysis - Escobar-Almeciga, Wilder Yesid; Brutt-Griffler, Janina (Íkala, Revista de Lenguaje y Cultura, 2022)
Bilingual learners often integrate semiotic resources and communicative modes across the languages they speak. Unfortunately, current approaches to researching such a phenomenon assign pragmatic functions to individual discourse moves at best or to isolated utterances at worst. Thus, using a social semiotic multimodal interaction analysis, this study examined actions in interactions of a group of six transnational students participating in a second-grade literacy circle at a school in western New York, USA. The purpose of this was to account for the complex reciprocities among their multimodal ways of communicating, their learning climate, and ultimately their learning as mediated and evidenced in their integrated multimodal communicative action. Data included four audio recordings of four literacy circle reading activities that took place during a four-day period. Findings suggest that, first, learning results from communication. Second, learning can only be evidenced through communication in interaction. Finally, communication is always multimodal and emergent while, at the same time, culturally governed. This presents direct implications for instruction and learning regarding the social conditions afforded to students to access their full repertoire of semiotic resources and modes to participate and act on their own behalf and in pursuit of their learning.